Effects of rapid and delay silo filling and 1177® silage inoculant on performance of growing cattle fed corn and sorghum silages. - Bolsen, K.; Ilg, H.; Hinds, M.; Milliken, George A.; Hoover, J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eight concrete stave silos (10 x 50 ft) were used in two trials to evaluate rapid (24 to 36 hr) and delay (15 days) filling, each with our without 1177® silage inoculant. Corn silage was used in Trial 1; forage sorghum in Trial 2. The delay-fill silages had a dry matter (DM) range of 34.4 to 39.9% in Trial 1 and 24.2 to 29.6% in Trial 1. All eight silages were well preserved with the four delay-fill silos having lower total fermentation acids than their rapid-fill counterparts. With corn silage, the rapid-fill silos had higher silage DM recoveries than the delay-fill silos. 1177® improved DM recovery in the rapid-fill silo but not in the delay-fill silo. With forage sorghum silage, the rapid-fill silos lost effluent which contributed to lower DM recoveries than in the delay-fill silos. 1177® improved DM recoveries with both fill procedures for the wetter sorghums. Steer performance was similar (P>.05) for all four treatments within each silage. When silage recovery and steer performance were combined, the 1177® treated silages produced more pounds of beef than their respective controls. When corn and forage sorghum silages were averaged, 1177® produced 3.3 lb more beef gain per ton of crop ensiled than uninoculated controls.
Keywords: Beef; Silo; Silage inoculant; Performance; Corn; Sorghum silage